Stimation of winter resistance of promising varities of tea in the conditions of warming winter period in Adygea - L. V. Vavilova (Новые технологии, 2018)
The article presents the results of the assessment of the dynamics of winter hardiness of promising forms of tea and the influence of the temperature factor on the degree of damage to the tissues of the shoots and leaves. The local change of the climatic system of the area has been analyzed and the issue of testing the variety forms under the warming conditions of the winter period have been considered in order to develop an adaptive assortment for the foothill zone of the Republic of Adygea based on the gene pool of the Adygh branch of FSBSI ARSRIFandGC.